LEARNING STRATEGIES FOR THE CONTENTS OF RHYTHMIC GYMNASTICS IN SCHOOL - Cristina ElenaMORARU; Alina RUSU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The paper focuses on the study of rhythmic gymnastics from a didactic perspective and on underscoring the field of artistic motricity of this discipline. The acquisition and appreciation of rhythmic gymnastics contents, in all its dimensions, may represent a way of attaining the objectives of school physical education and sport. The coaches, teachers, scientists, and students make up a group of competent persons who, through their diversity, enrich and contribute to the development of this discipline. The purpose of this paper is to outline learning strategies concerning mainly the passage from the notion of "acting" to the notion of "knowing how to act" in real situations. Hence, we wish to empower the students to create and bring their own solutions, to be the promoters of their motor transformations. Discussions. The intervention concerning the technical-artistic dialectics, the learning strategies, and the analysis instruments outlined here acts upon the acquisition method of rhythmic gymnastics contents and the formulation of operational recommendations. The conclusions of this paper are materialized in answers to certain questions that any beginner or expert asks at a certain point: What competencies can we develop in a child? How can we turn the student into an "actor" of his own transformations? What situations can we propose for stimulating progress? Conclusions. The objective of learning is to ensure the passage from previous possibilities to new possibilities, and this passage takes into account the resources and rhythm of every child. In order to allow these passages, a teacher must provide to the student a didactic environment adequate to the construction of his transformations. Therefore, the paper provides to teachers and coaches necessary reference points and strategies for designing and applying a training practice that allows them to be bold and to succeed.